Novel broadband circularly polarized pentagonal printed antenna design for wireless power transmission applications - Walid En-Naghma; Hanan Halaq; Abdelghani El Ougli (Institute of Advanced Engineering and Science, 2023)
This paper provides a new conception for a microstrip patch antenna array that operates in a circularly polarized manner for wireless power transmission (WPT) at 2.45 GHz. The proposed conception combines four pentagonal patches and the defected ground structure (DGS) method. The antenna array with a dielectric constant of 4.4 and a tangential loss of 0.025 is printed on a FR4 where its thickness is about 1.58 mm. The developed design aims to optimize the antenna array performance. Th e main contribution, to the telecommunications and WPT fields, is to achieve a maximum energy transfer with low losses, while also ensuring adequate adaptation to the excitation port. To prove the effectiveness of this design, simulation results were obtai ned using computer simulation technology microwave studio (CST MWS) software and validated by another solver high - frequency structure simulator (HFSS). Simulation results are presented and compared with those obtained using existing conceptions in the lite rature. The proposed design has proven to be very effective in achieving the intended objectives, which makes this design very good for radiofrequency (RF) energy collection and its various applications to power a variety of devices without harming our pla net.